2021
DOI: 10.3390/foods10102304
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of the Essential Oil Extracted from Elsholtzia densa and Their Insecticidal Activity against Tribolium castaneum and Lasioderma serricorne

Abstract: Storage pests pose a great threat to global food security. Here, we found that the essential oil (EO) extracted from E. densa possesses obvious effects against the insects that threaten stored-products. In this work, we investigated the chemical constituents of the essential oil extracted from Elsholtzia densa, and their insecticidal (contact and fumigant) toxicity against Tribolium castaneum and Lasioderma serricorne. A total of 45 compounds were identified by GC-MS, accounting for 98.74% of the total EO. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
(47 reference statements)
2
11
0
Order By: Relevance
“…Meanwhile, Table 3 shows that the LD 50 of the contact activity against L. serricorne adults of plant essential oils in rosemary, geranium, citronella, basil, and eucalyptus are 3.60, 3.49, 8.90, 6.70, and 7.80 μl/L, respectively, which are even better than those of Pirimiphos-methyl (15.45 μl/L) and Chlorantraniliprole (249.77 μl/L). In recent years, many research studies on the essential oils against L. serricorne have been performed, for example, Liang et al (2021) found that Elsholtzia densa essential oil possesses obvious contact activity (LD 50 = 24.29 mg/L) against L. serricorne . Meanwhile, Zhou et al (2018) reported that the Artemisia lavandulaefolia (Compositae) essential oil also exhibited good contact toxicity (LD 50 = 13.51 μg/L) to control L. serricorne .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Table 3 shows that the LD 50 of the contact activity against L. serricorne adults of plant essential oils in rosemary, geranium, citronella, basil, and eucalyptus are 3.60, 3.49, 8.90, 6.70, and 7.80 μl/L, respectively, which are even better than those of Pirimiphos-methyl (15.45 μl/L) and Chlorantraniliprole (249.77 μl/L). In recent years, many research studies on the essential oils against L. serricorne have been performed, for example, Liang et al (2021) found that Elsholtzia densa essential oil possesses obvious contact activity (LD 50 = 24.29 mg/L) against L. serricorne . Meanwhile, Zhou et al (2018) reported that the Artemisia lavandulaefolia (Compositae) essential oil also exhibited good contact toxicity (LD 50 = 13.51 μg/L) to control L. serricorne .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, other Rhododendron plants had also been reported to have contact activity against these three insects. Such as the EO extracted from the R. thymifolium and its principal Germacrone had good contact activity against L. serricorn adults, larvae and T. castaneum larvae with LD 50 values of 29.15 μg/adult, 42.73 μg/larva, 19.65 μg/larva, respectively [22] …”
Section: Resultsmentioning
confidence: 99%
“…For example, EO of R. anthopogonoides have been reported to possess insecticide and fumigant activities against S. oryzae , and its main component 4‐Phenyl‐2‐butanone shows pronounced contact toxicity against S. oryzae [21] . The EO of R. thymifolium possessed the obvious repellent and contact activities against the T. castaneum and L. bostrychophila , and the presence of permafrost might be one of the key factors affecting the contact toxicity of R. thymifolium EO against T. castaneum and L. bostrychophila [22] . There four EOs from Rhododendron species, including R. capitatum , R. przewalskii , R. mucronulatum , and R. micranthum has been reported to have repellent activities against T. castaneum , L. serricorne and L. bostrychophila adults, and within a certain concentration range, the repellent activities show a certain stability [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the chemical constituents detected in R. przewalskii EO reported in this paper were consistent with the previous studies (Bai et al 2019 ). Compared with the other Rhododendron plants, these two EOs were also found rich in terpenoids, while the types and contents of terpenoids were different; for example, the content of β-Elemenone was 0.84% in the specie of R. Rufum in this experiment, whereas β-Elemenone (35.17%) had a high content in the specie of R. thymifoliu (Liang et al 2021a , b ). Spathulenol (14.4%), one of the main components isolated in the EO of R. albiflorum leaves, is only 0.71% in the species of R. przewalskii (Schepetkin et al 2021 ).…”
Section: Discussionmentioning
confidence: 66%
“…In view of the above situations, a series of measures have been taken to prevent pest risks. The most commonly used method is the application of synthetic chemicals (Liang et al 2021a , b ). For example, phosphine fumigants and pyrethroids contact insecticides have been widely used for controlling insects in stored products worldwide (Nayak et al 2020 ; Campolo et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%